Analysis of Weed Vegetation in Robusta Coffee (Coffea robusta L.) Traditional Farm at Pesawaran, Lampung - Nindy Permatasari; Made Same; Resti Puspa Kartika Sari; Lu'lu' Kholidah Fauziah (Jurnal Biologi Tropis, 2023)
Weeds are highly undesirable plants in plantation areas, including robusta coffee plants. This is as a result of the presence of weeds that might minimise the productivity of robusta coffee plants. Currently, various types of weeds found in robusta coffee plants are known. This study aimed to enumerate the types of weeds found in robusta coffee plants. The research was conducted in June 2023 in robusta coffee plantations in Wiyono Village, Gedong Tataan, Pesawaran, Lampung Province. The research was conducted by purposive sampling with the plot method. The analysis showed that the composition of weeds in coffee plants consisted of 9 families and 14 species. Ageratum conyzoides appeared to dominate the coffee plants with the highest Summed Dominance Ratio (SDR) value (46.08%).  The weeds diversity index (H') in coffee plants was 0.823 and the dominance index was 0.636576.